Brushless DC motor‐driven grid‐interfaced solar water pumping system. Issue 12 (1st October 2018) - Kumar, Rajan; Singh, Bhim
Abstract : A solar water pumping system employing a brushless DC motor drive is presented. The utility grid is utilised as a secondary power source. The total load demand is shared by photovoltaic array and the grid. This results in continuous water pumping. The amount of power shared by each source is controlled through a power factor corrected boost converter. The full utilisation of motor pump is achieved with increased reliability. The power quality is improved at the utility grid side. The simulation and hardware implementation are carried out to exhibit the performance of the system.